Preparation of New Copolyesters Based on Dibenzylideneacetone Moiety (Journal of Academic Research, 2020)
A series of four unsaturated copolyesters were prepared by interfacial polycondensation technique of 1,3-bis(4-hydroxy-3-methoxybenzylidene) acetone I or 1,3-bis(4-hydroxybenzylidene) acetone II with 3,3\-isophthalate dibenzoyl chloride V and 4,4\-isophthalate dibenzoyl chloride VI. Initially, the two diphenols I, II were prepared by reacting two equivalents of 4-hydroxy-3-methoxybenzaldehyde or 4-hydroxy benzaldehyde with one equivalent of acetone in the presence of a catalytic amount of concentrated HCl and EtOH as a solvent at reflux. The resulting copolyesters were characterized by elemental analyses; IR; Solubility and Rate of water absorption.